The prevalence of suicides in Lithuania - Domanskienė, V.; Gailienė, D. (Psichologija, 1993)
The article presents epidemiological data of years 1924-1991. This data analysis showed the before the war suicide level was low, even lower than in the neighboring countries, for example, Estonia. During the years of soviet occupation, the number of suicides has grown constantly and reached its pinnacle in 1984. During the reform movement, this number decreased significantly, but it is beginning to increase recently. The number of suicides in villages and among middle-aged men is especially large. The data is discussed with the reference to Dukheim theory.
Keywords: suicide; number of suicides; Durkheim